Design and Manufacture of Free Fall Impact Test Equipment with Drop Weight Test model. - Mahyunis; Nurdiana; Farah Dina, Sari; Wito Pirmansyah, Ahmad (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
The rapid development of technology today is a challenge that must be considered by making technology itself. However, not many pay attention to the qualified aspects that must be in technology. Which can have a bad influence on the work environment. Therefore, this study aims to obtain a re-design and model of a free fall impact test equipment, obtain the main components of a free fall impact test equipment with the drop weight test method and obtain a manufacturing process. This design method uses Autocad software and Ansys Workbench Simulation 14.5. Based on the simulation results, the free fall impact test equipment with the number of each component, namely: 3-node and 4-node. The difference between theoretical calculations and simulation calculations in each component, namely the main structure pole, obtained voltage 1,455, voltage 1.345 and Poisson ratio 0.7, the launcher pipe obtained voltage 1.451, voltage 1.346, Poisson ratio 0.04 and friction coefficient 265.10, anvil table obtained voltage 1.248, Poisson ratio 0.02 and Safety factor 11. The work on the free fall impact test equipment has a manufacturing time of 54.1 minutes.